Self‐Powered High‐Detectivity Lateral MoS2 Schottky Photodetectors for Near‐Infrared Operation. (25th January 2021) - Mao, Yichen; Xu, Pengpeng; Wu, Qiang; Xiong, Jun; Peng, Renmiao; Huang, Wei; Chen, Songyan; Wu, Zhengyun; Li, Cheng
Abstract: 2D transition metal dichalcogenides (TMDs) have been widely investigated for possible application in field‐effect transistors and optoelectronic devices. However, due to the wide band gap of most TMDs, photoresponse to infrared wavelength is still a big challenge. Here, a lateral molybdenum disulfide (MoS2 )‐on‐metal Schottky photodetector operating in internal photoemission mode for near‐infrared wavelength with high responsivity is reported. With moderate Schottky barrier height, a low dark current of 0.12 nA at −0.5 V and a remarkable rectification ratio of 10 3 at ±0.8 V are realized in the MoS2 ‐on‐Au Schottky photodetector. The maximum responsivity of 1.9 A W −1 at −1 V is achieved at 1310 nm due to the photoemission from the underlayering Au electrode, which absorbs most of the incident light through the transparent MoS2 layers, and the generated photocurrent gain in MoS2 layers. Furthermore, the MoS2 Schottky photodetectors are self‐powered. The high responsivity of 0.68 A W −1 and the excellent specific detectivity of 1.89 × 10 12 Jones at 1310 nm are obtained under 0 V. The excellent performance demonstrates that internal photoemission mechanism can be well applied in 2D material Schottky photodetectors for infrared wavelengths. Abstract : A lateral self‐powered MoS2 ‐on‐metal Schottky photodetectors operating in the internal photoemission mode for near infrared wavelength with high responsivity is reported. In the MoS2 ‐on‐Au Schottky photodetectors, the high responsivity of 0.68 A W ‐1 and the excellent specific detectivity of 1.89 × 1012 Jones at 1310 nm are obtained for the devices under 0 V.